Feeding strategy of juvenile (age-0+ year) Argentine hake Merluccius hubbsi in the Patagonian nursery ground - Temperoni, Brenda (2013)
Age-0+ year juvenile Argentine hake Merluccius hubbsi (60–150 mm total length, LT) from San Jorge Gulf, north Patagonian shelf region of the Argentine Sea, had an almost exclusively pelagic diet dominated by the hyperiid amphipod Themisto gaudichaudii and the euphausiid Euphausia lucens. This suggested that final settlement and permanent demersal habitat utilization might not, as previously reported, occur at earlier sizes (c. 20 mm LT). Their feeding strategy involves specialization at a population level towards both the main pelagic prey, indicating a narrow trophic niche. Novel data are provided which contribute to the growing body of information in relation to the age-0+ year transitional stage in demersal fishes and particularly to M. hubbsi recruitment in the Argentine Sea.